Pengaruh Model Pembelajaran Think Pair and Share Terhadap Motivasi Dan Hasil Belajar IPA Terpadu SMP Negeri 1 Gunungsitoli Utara Tahun Pembelajaran 2023/2024 - Pewirman Hulu (Program Studi Pendidikan Biologi - Universitas Nias, 2023)
This study aims to determine the effect of implementing the Think Pair and Share (TPS) learning model on students’ motivation and learning achievement in Integrated Science, particularly focusing on the topic of plant tissue structure and organs. A quantitative approach with an experimental method and a randomized control-group pretest-posttest design was applied in this study. The research population included all eighth-grade students at SMP Negeri 1 Gunungsitoli Utara, consisting of seven classes. Through random sampling, class VIII-C (21 students) was selected as the experimental group implementing the TPS model, while class VIII-F (19 students) served as the control group using a conventional model. Data were collected using essay-based test instruments to measure cognitive learning outcomes and questionnaire instruments to assess learning motivation levels. The data were then analyzed using parametric hypothesis testing (t-test and Z-test) after meeting prerequisite tests of normality (Lilliefors test) and homogeneity (Harley test). The results showed that the average learning outcome of the experimental group reached 81.43 (good category), significantly higher than the control group, which scored 72.21 (fair category). Hypothesis testing indicated the rejection of the null hypothesis (H0), with t_calculated (3.869) > t_table (1.686) for learning outcomes, and Z_calculated (1.71) > Z_table (1.64) for learning motivation, which reached 88.19%. Thus, it can be concluded that the Think Pair and Share learning model has a significant positive effect on both motivation and learning outcomes. The implications of this study highlight the importance for educators to implement varied and interactive cooperative learning models in order to enhance communication, engagement, and active participation of students in the learning process.